Analisis Dan Perancangan Alat Pendeteksi Tekanan Kerja Pompa Bahan Bakar Efi (Electronic Fuel Injection) Dengan Menggunakan Sensor Tekanan - Toto Sugiarto -; Andrizal - -; Yandri Anto - (Jurnal Ilmiah Poli Rekayasa, 2015)
An EFI cars (Electronic Fuel Injection) is not equipped with a pressure fuel pump indicator, so the driver does not know the the fuel pump performance. If the fuel pump work under the standard, the engine is not responsive to acceleration, engine temperature can be increased and the performance of the engine is lowered. This research are trying to design a fuel pump pressure detector using a pressure sensor. The research methodology used is the Research and Development (R & D) consisting of product design, design validation, design revisions, and test products. This study used three product design because the design of the first and the second has not been as expected. The third design uses a comparator circuit as the controller three indicator LED (Light Emitting Diode). If the fuel pump working pressure of 2,1kg / cm²-2.5 kg / cm², the three colored LED green, yellow and red lights up. If the fuel pump working pressure of 1.6 kg / cm²-2,0kg / cm², the two LED will light up the colors yellow and red. If the fuel pump working pressure of 1,0kg / cm²-1.5 kg / cm², it is only one red LED are illuminated. A comparison between the changes in pressure to produce the output voltage linear data and repeatibility = 0.